The impact of interactive multimedia incorporating local cultural content and project-based learning on Junior High School Student writing skills - Nur Indah Sari, Vina; Sarwiji Suwandi; Sumarwati (Research Journal in Advanced Humanities, 2024)
This study investigated the effectiveness of interactive multimedia incorporating local cultural content and Project-Based Learning (PBL) on the writing skills of junior high school students. Utilizing a quasi-experimental design with a non-equivalent control group, the research involved pre-tests and post-tests for both experimental and control groups. The experimental group engaged with the Pontdaloka application, an interactive multimedia tool enriched with Pontianak's local cultural elements, while the control group utilized traditional PowerPoint presentations. Data analysis using independent sample t-tests revealed a significant improvement in students' writing skills in the experimental group, with a significant value (2-tailed) of 0.003, t-score of 3.043, and t-table of 1.671. These findings suggest that interactive multimedia combined with local cultural content and PBL enhanced students' writing skills more effectively than conventional teaching methods. The study underscores the importance of integrating local culture in educational media to create engaging and relevant learning experiences, thereby improving academic performance and fostering a deeper appreciation for cultural heritage.